Perspectives on the socio-economic challenges and opportunities for tree planting: A case study of Ethiopia - Boissière, M.; Atmadja, S.; Guariguata, Manuel R.; Kassa, H.; Sist, P. (Elsevier, 2021)
We reflect on the socio-economic challenges in designing, implementing and monitoring tree planting activities using a case study of Ethiopia, a country aiming to restore 15 of the 127.7 million hectares (ha) pledged by 31 African countries as of June 2021. Based on a literature review and expert assessments, we describe and analyse the historical context of both deforestation and afforestation and reforestation in Ethiopia. We also assess the extent to which the socio-political environment in Ethiopia enables successful tree planting based on a set of socio-economic drivers known to affect tree planting outcomes. We find that, overall, there is a need to pay more attention to the socio-economic dimension of tree planting, in particular to fully consider both the needs and participation of local communities. We also perceive a high risk of afforestation being misidentified as reforestation; insufficient consideration of local community participation, benefit sharing and land tenure issues; and insufficient marketing for forest products derived from planted and natural forests. We recommend: (i) raising awareness about the risk of confounding afforestation and reforestation, and developing approaches to manage those risks; (ii) promoting bottom-up approaches to tree planting, to complement existing top-down approaches; (iii) assisting local communities in securing long-term rights and benefits over land, in setting objectives and in accessing the means for implementing tree planting; and (v) improving financial returns from tree planting activities while creating opportunities for the private sector.